Is green certification the solution to substandard indoor air quality (humidity)? A case study of old, new and green-certified dwellings. Issue 2 (3rd April 2021) - Ade, Rochelle; Rehm, Michael
ABSTRACT: New Zealand is hamstrung by a housing crisis. Although the discourse primarily focuses on housing affordability and homelessness, there is a more pervasive problem afflicting New Zealanders: that New Zealand homes are substandard, being cold, damp and difficult to heat. This article reviews the moisture levels of three categories of housing (older vintage, newly constructed and newly constructed green certified) in Auckland, New Zealand, to determine whether the pervasive issue of high internal humidity in housing can be successfully rectified through using a green building certification. The results show that newly constructed 6-Homestar dwellings are in the optimal relative humidity range mean 14 per cent of time in contrast to 17 per cent for new code-compliant dwellings (and six per cent for older vintage dwellings) in the damp winter months of June through August. This research documents that a particular green certification – 6-Homestar – may not deliver suitable humidity control, and that alternative certifications that stipulate airtightness levels and require active ventilation – such as Passive House – could be considered by policy makers interested in delivering low-carbon, warm, dry houses in New Zealand.